'Civilizing' the pastoral frontier: land grabbing, dispossession and coercive agrarian development in Ethiopia. Issue 5 (29th July 2019) - Regassa, Asebe; Hizekiel, Yetebarek; Korf, Benedikt
ABSTRACT: This paper analyzes frontier dynamics of land dispossessions in Ethiopia's pastoral lowland regions. Through a case study of two sedentarization schemes in South Omo Valley, we illustrate how politics of coercive sedentarization are legitimated in the 'civilizing' impetus of 'improvement schemes' for 'backward' pastoralists. We study sedentarization schemes that are implemented to evict pastoralist communities from grazing land to be appropriated by corporate investors. It is argued that frontier imaginations of pastoral lowlands legitimate coercive practices of 'emptying' the lowlands for investments. 'Improvement schemes' enroll private investors and enterprises affiliated with Ethiopia's ruling party in the politics of 'thickening' state presence in the pastoral frontier. Agricultural extension packages serve to expand state control over sedentarized pastoralists and make lowland resources more extractable, for investors and for the ruling regime.